Pendampingan Pemanfataan Media Sosial Sebagai Sarana Digital Branding pada Pondok Pesantren Al-Muin Syarif Hidayatullah - Meutia, Nur Shabrina; Sulistiyani, Endang; Kurniastuti, Ima; Sari, Rita; Lukiyono, Yauwan Tobing (Universitas Islam Nahdlatul Ulama Jepara, 2023)
Digital Branding in educational institutions is very crucial to do because it will improve reputation and form an institutional brand image. Regarding the use of digital technology in the Al-Muin Islamic Boarding School environment, currently, it can be said to be very low. This stated shows from the lack of social media owned by the Al-Muin Islamic boarding school. Meanwhile, with social media, the boarding school will be able to communicate and build public relations with the society. Having a relationship with the society will improve the good image of the Islamic boarding school and also as a medium of communication for the boarding school with the soociety. The implementation team of community service activities will assist in the use of social media as a means of digital branding at the Al Muin Syarif Hidayatullah Islamic Boarding School. The teams activity are carried out in four stages, namely: initiation, preparation of facilities and infrastructure, execution and evaluation. The comparison of the pre-test and post-test results shows an increase in the level of understanding of the caregivers of the Al Muin Syarif Hidayatullah Islamic Boarding School in using social media Instagram as a means of digital branding.